Increasing Technical Justification for University’s Data Center Development - Prabowo, I Putu Deny Arthawan Sugih; Abdullah, Riska Kurniyanto; Suweden, I Nengah; Seppang, Yesi Destri; Prambudi, Dwi Arief; Sulistyawati, Arum Kurnia; Utomo, M. Chandra Cahyo; Putra, Jeffry Andhika; Sudarni, Adiek Astika Clara (International Journal of Informatics and Computation, 2026)
Resilient information technology (IT) infrastructure is required for the digitalization of higher education to support essential academic and administrative IT services. XYZ University faced significant challenges due to vulnerabilities in its existing data center, which lacked standardized technical qualifications and was susceptible to single points of failure. This study formulated a comprehensive technical justification for developing a Tier-3 data center by synthesizing the technical references/standards and adapting risk management best practices from the Indonesian banking sector. The findings indicated that in achieving concurrent maintainability and 99.982% availability, critical infrastructure requirements must be met in the architectural, electrical, mechanical (HVAC), and telecommunications domains. N+1 redundancy, 500 kVA backup power, and grounding of less than 1 ohm are all important parts that keep XYZ University’s important IT services, such as SIAKAD and LMS, safe. These justifications served as the foundational reference for the institutional Disaster Recovery Plan (DRP). The study concluded a Rector’s Decree that incorporates technical references/standards into strategic strategy offers a strong governance framework for the academic community as a whole to ensure long-term digital resilience and the continuity of IT services.